(untitled) - Schotten, Kees (Wageningen, 1991)
This report is the result of a four month thesis in scope of the VH-10 project, a cooperation between Wageningen Agricultural University and the University of Can Tho, Vietnam. This study aims at elaborating economic data and farming systems information into factors that are important to (future) land use and crop production. Both the gathered socio-economic and the physical data are implemented in a database. On this database queries ( questions ) were performed to analyze the farming systems in the study area, and relationships between physical and socio-economic factors
Keywords: Drainage,Irrigation farming,Soils; Mekong river delta; Vietnam